Unusual Anatomy of Maxillary Second Premolars - de Almeida-Gomes, Fábio; de Sousa, Bruno Carvalho; de Souza, Fabricio Dias; dos Santos, Roberto Alves; Maniglia-Ferreira, Cláudio (European Journal of Dentistry, 2009)
In this study, endodontic treatments of maxillary second premolars with unusual anatomical configuration were presented. Maxillary second premolars usually have one root with one or two root canals. The occurrence of variations in anatomical configuration is also common; therefore, it must be taken into account in clinical and radiographic evaluation during the endodontic treatment. These teeth may also require special shaping and filling techniques. This article reports and discusses the treatment recommendations for unusual occurrences of anatomical configurations in four different maxillary second premolars. (Eur J Dent 2009;3:145-149)
Keywords: Dental anatomy; Root canal; Maxillary second premolar